Effects of a psychological intervention on the quality of life of obese adolescents under a multidisciplinary treatment - Camila R.M. Freitas; Thrudur Gunnarsdottir; Yara L. Fidelix; Thiago R.S. Tenório; Mara C. Lofrano-Prado; James O. Hill; Wagner L. Prado (Elsevier, 2017)
Objective: To investigate the effects of multidisciplinary treatment with and without psychological counseling on obese adolescents' self-reported quality of life. Methods: Seventy-six obese adolescents (15.87 ± 1.53 y) were allocated into psychological counseling group (PCG; n = 36) or control group (CG; n = 40) for 12 weeks. All participants received the same supervised exercise training, nutritional and clinical counseling. Participants in PCG also received psychological counseling. QOL was measured before and after 12 weeks of intervention by Generic Questionnaire for the Evaluation of Quality of Life (SF-36). Results: The dropout rate was higher in GC (22.5%) when compared with PCG (0.0%) (p < 0.001). After 12 weeks, participants from PCG presents lower body weight, relative fat mass and higher free fat mass (p < 0.001 for all) compared to GC. QOL improved among adolescents from both groups (p < 0.05), however, a better QOL was reported from those adolescents enrolled in PCG. Conclusion: The inclusion of a psychological counseling component in multidisciplinary treatment for adolescent obesity appears to provide benefits observed for improved QOL as compared with treatment without psychological counseling. Resumo: Objetivo: Para investigar os efeitos do tratamento multidisciplinar com e sem aconselhamento psicológico voltado à qualidade de vida de adolescentes obesos. Métodos: 76 adolescentes obesos (15,87 ± 1,53 ano) foram alocados em um grupo de aconselhamento psicológico e (GAP; n = 36) ou grupo de controle (GC; n = 40) por 12 semanas. Todos os participantes receberam o mesmo treinamento físico supervisionado e aconselhamento nutricional e clínico. Os participantes no GAP também receberam aconselhamento psicológico. A qualidade de vida foi avaliada antes e depois das 12 semanas de intervenção por meio de um Questionário Genérico de Avaliação da Qualidade de Vida (SF-36). Resultados: O abandono do tratamento foi maior no GC (22,5%), em comparação ao GAP (0,0%) (p < 0,001). Após 12 semanas, os participantes do GAP apresentam menor peso corporal, massa gorda relativa e maior massa livre de gordura (p < 0,001 para todos) em comparação ao GC. A qualidade de vida melhorou entre os adolescentes de ambos os grupos (p < 0,05); contudo, uma melhor qualidade de vida foi relatada pelos adolescentes incluídos no GAP. Conclusão: A inclusão de aconselhamento psicológico no tratamento multidisciplinar dos adolescentes obesos parece proporcionar benefícios observados na melhoria da qualidade de vida, em comparação ao tratamento sem aconselhamento psicológico. Keywords: Multidisciplinary intervention, Obese adolescents, Psychological counseling, Palavras-chave: Intervenção multidisciplinar, Adolescentes obesos, Aconselhamento psicológico